Risk factors associated with severe early childhood caries - Siquero-Vera, Kariem Noelia Sherezade (2018)
Early Childhood Caries (ECC) is considered a public health problem; when it is not treated in a timely manner, the disease progresses to a severe level. Currently there are many studies on the prevalence and risk factors of ECC, but little on the issue of Severe Early Childhood Caries (S-ECC). The present review article evaluates the different factors that have been related to S-ECC, in recent years, grouped into three major areas: host, microorganism and substrate. A search was made in the LILACS, Medline and Elsevier database; from the year 2010 with the keywords Caries of Severe Early Childhood, risk factors, Severe Early Childhood Caries and risk factors